Archival documents on placenames of Tuvan municipalities (1759–2005) - Hovalyg, Salimaa S.; Darzha, Urana A. (The New Research of Tuva, 2020)
The article analyzes almost every document found at the National Archives (prior to 07.04.2020 known as the State Archives) of the Republic of Tuva which mentions placenames of 49 Tuvan municipalities. These documents were originally drawn by local authorities and refer to their administrative practices. We examine the origin of these toponyms and their subsequent changes, with our retrospective analysis of the evolution of placenames of Tuvan municipalities covering the documents made between 1759 and 2005. The list of municipalities includes the rayons of Tuva as the region’s territorial units, and separate settlements, from those founded at the first arrival of the Russian merchants to the towns of Kyzyl, Chadan, Ak-Dovurak, Shagonar and Turan. There are four stages in the rise and development of territorial division of Tuvan lands: 1) 1759–1921; 2) 1921–1944; 3) 1944–1991; and 4) 1992 to present, with the most recent document in our selection dated 2005. The documents written during the first stage appear in Old Mongolian and follow the rules of Chinese record keeping. Later documents were written in Tuvan or Russian. Statebuilding, administrative reforms, and the creation or recreation of political and social institutions were the factors that helped change some of the Tuvan toponyms. The borders of the rayons were frequently changed, new rayons were created and then gave way to more recent ones, and new administrative centers appeared. Renaming followed the linguistic norms active at the moment.